Effect of Strawberry Juice (Fragaria Ananassa) on Mechanical Properties of Nanofilled Composite Resins - Kusnadi, Stephanie Justine; Margaretta, Dewi Liliany; Tjandrawinata, Rosalina (Journal of Indonesian Dental Association, 2023)
Introduction: Nanofilled composite resins have small filler particles size (1-100 nm). Its mechanical properties consist of hardness, surface roughness, and water absorption. Composite resins easily degraded by acid pH because it contains polymer with unstable bonds. Degradation can cause water absorption. It can be scratched more easily if they have low hardness. Rough surfaces can cause the risk of plaque formation, secondary caries, discoloration, damage to the surface of the patch, reduces resistance, accelerates abrasion, and can cause irritation to the surrounding soft tissue. Objective: To analyze the effect of mechanical properties (water absorption, hardness, and surface roughness) on nanofilled composite resins after strawberry juice (Fragaria ananassa) immersion. Methods: This research was a laboratory experimental with post-test and control group design. Forty cylindrical samples of nanofilled composite resins Filtek Z350XT (3M ESPE) (10mm x 2 mm) were divided into four groups: water absorption group, hardness tested group, surface roughness tested group, and control group. Surface roughness tested group and hardness tested group were immersed in strawberry juice each 10 mL for 2 hours a day and repeated for 12 days. After 10 and 12 days of immersion, hardness tested group, surface roughness tested group, and control group will be measured using surface roughness test and hardness test. Water absorption test will be carried out before immersion and after 10 and 12 days of immersion. Results: One Way ANOVA statistical test on surface roughness test showed a p-value of 0.001 (p<0.05) and the water absorption test show a p-value of 0.983 (p>0.05). Post Hoc Tukey test had significant difference of roughness tested on day 12 and control group with a p-value of 0.01 (p<0.05). Conclusions: Strawberry juice increases surface roughness of nanofilled composite resins after 2 hours immersion for 12 days in comparison with control group.